Specialized Rehabilitation Centers (CER) in the SUS and the impact of the covid-19 pandemic - Suda, Bianca Tomi Rocha; Mota, Paulo Henrique dos Santos; Bousquat, Aylene (Revista de Saúde Pública, 2023)
OBJECTIVE: To analyze the impact of the covid-19 pandemic on the functioning of Specialized Rehabilitation Centers (CER) in the SUS. METHODS: An analysis of the variation in outpatient production of the CER was carried out based on data from the Outpatient Information System of the Unified Health System (SIA-SUS) from March 2019 to December 2021. Such results were compared with CER managers' perceptions about the impacts of the pandemic on the units, measured by a web survey applied between November 2020 and February 2021. Monthly averages of 247 procedures were calculated, organized into 18 groups, for three periods – year before the pandemic (YBP) and first (YP1) and second (YP2) years of the pandemic. Through the online form, information was collected on: operation and organization of services; post-covid-19 rehabilitation; actions to support the needs of users and professionals; strategies and challenges experienced. RESULTS: There was a 33.3% reduction in the total number of procedures in YP1 compared to YBP. There were no reductions in procedures performed by nurses and for ostomates. There was greater impairment for group activities, visual therapies and home visits. In YP2, there was a recovery of averages in relation to YBP in 11 groups of procedures, with an increase of 104.1% in Cardiorespiratory Physiotherapy. In the answers to the online form, 91.7% of the managers indicate structural and/or organizational changes in the CER, such as: creation of prioritization criteria for assistance; introduction of telerehabilitation; changes in the work process and; provision of professional training. Half of the CER already treated people with covid-19 sequelae, but not all of them had been trained to do so. Limitations in participation and social support for PWD were identified. CONCLUSIONS: There was a severe impact of the covid-19 pandemic on the CER. Added to the damming up of previous demands are those of post-covid-19 users, configuring a challenging picture. It is necessary to strengthen the Care Network for Persons with Disabilities, with expansion and greater integration of services and a more inclusive organization to overcome these challenges.